The Role of Gratitude on Life Satisfaction for Adolescents in Malang City Orphanages - Pertiwi, Bestarindra Ramadhania; Harsono, Yudi Tri (Universitas Negeri Malang, 2023)
This research aims to examine the role of gratitude in the life satisfaction of adolescents in orphanages in Malang City. This research uses a quantitative approach with a correlational design, using simple linear regression analysis techniques. The population of this study was adolescents in orphanages in Malang City. The sample used in this research was 223 people selected using incidental sampling techniques. Data collection used the Gratitude Questionnaire-Six-Item Form (GQ-S6), which was adapted into Indonesian by Grimaldy and Haryanto (2020) and adapted the Satisfaction with Life Scale (SWLS) in Adolescents based on the concept of Diener et al. (1985). The results obtained show that gratitude plays a role in the life satisfaction of orphanage youth in Malang City, with an F value of 32.817 and a significance of (3.289 ×10-8) more than 0.05, so the gratitude variable can predict the life satisfaction variable for adolescents in orphanages in Malang City.